Clinical feasibility of miniaturized Lissajous scanning confocal laser endomicroscopy for indocyanine green-enhanced brain tumor diagnosis - Hong, Duk Hyun; Kim, Jang Hun; Won, Jae-Kyung; Kim, Hyungsin; Kim, Chayeon; Park, Kyung-Jae; Hwang, Kyungmin; Jeong, Ki-Hun; Kang, Shin-Hyuk (Frontiers in Oncology, 2023)
Intraoperative real-time confocal laser endomicroscopy (CLE) can be an alternative modality for frozen tissue histology that enables visualizing the cytoarchitecture of living tissues with spatial resolution at the cellular level. We developed a new CLE with “Lissajous scanning pattern” and conducted a study to identify its feasibility for fluorescence-guided brain tumor diagnosis. Conventional hematoxylin and eosin (H&E) histological images were compared with indocyanine green (ICG)-enhanced CLE images in two settings: (1) in vitro and ex vivo glial tumors of mice and (2) surgically resected human brain tumors. The cultured U87 and GL261 tumor cells were implanted into the mouse brain, and the H&E stains were compared with CLE images at normal and tumor tissue ex vivo. To determine the invasion of the normal brain, two patient-derived glioma cells were used for orthotopic tumor formation and compared using two methods (CLE vs H&E staining). In human brain tumors, specimens from 69 patients were prospectively obtained after elective surgical resection and were also compared. The comparison was performed by an experienced neuropathologist. In the incubation of ICG in vitro, U87 and GL261 cell morphologies were well defined in the CLE images and depended on dimethyl sulfoxide (DMSO). In the ex vivo examination of xenograft model, dense and heterogeneous glioma cell cores and peri-lesional necrosis was well defined in both methods. In patient-derived glioma xenograft models, invasive tumor cell clusters were well identified in CLE images, which corresponded to H&E staining. In human brain tumors, CLE images well visualize the cytoarchitecture of the brain and tumor tissues and the pathognomonic microstructures according to the tumor subtypes were also clearly observed. Interestingly, in glioma, the cellularity of the tumor and the density of streak-like patterns were significantly associated with tumor grade in the CLE images. In addition, panoramic view reconstruction was successfully conducted for visualizing a gross tissue morphology. In conclusion, newly developed CLE with Lissajous laser scanning can be a helpful intraoperative device for real-time diagnosis, detection of tumor-free margins, and maximal safe resection of brain tumors.